(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2017)
The paper aims to provide a reflection about the different types of models of urban growth in relation to the territorial social context, it means an investigation about those relationships established between spatial environment and human connection which often, and specifically in recent years, have generated not a few conflicts in the balance among spatial and social combination. Definitely, the urbanization process is affected by geographic factors, but if we look at how urbanization has spread over territory during the last ten years, and we concentrate on its forms of occupying the soil, we have the clear suspect that urbanization in Tunisian areas, has underwent a process of uncontrolled and uncoordinated planning without care for environmental problems. By the use of space syntax analysis, the research aims to identify and assess the new types of urban forms that emerged in by the processes of socio-spatial transformations and analyses landscape identities that are emerging in fragmented areas as a sort of reconfiguration and territorial differentiation on the edge of cities. We took as example the case of the city of Monastir, located on the coast of Tunisia. Our objective is to show the process of urban landscape and to review the new territorial actions and identities that came with the socio-spatial reconfiguration of the city. The evolution of contemporary city of Monastir may be illustrated in relation to its territory: its geographic impact may be investigated within urban landscapes through a social approach.